2014
DOI: 10.1371/journal.pntd.0002696
|View full text |Cite
|
Sign up to set email alerts
|

A Monoallelic Deletion of the TcCRT Gene Increases the Attenuation of a Cultured Trypanosoma cruzi Strain, Protecting against an In Vivo Virulent Challenge

Abstract: Trypanosoma cruzi calreticulin (TcCRT) is a virulence factor that binds complement C1, thus inhibiting the activation of the classical complement pathway and generating pro-phagocytic signals that increase parasite infectivity. In a previous work, we characterized a clonal cell line lacking one TcCRT allele (TcCRT+/−) and another overexpressing it (TcCRT+), both derived from the attenuated TCC T. cruzi strain. The TcCRT+/− mutant was highly susceptible to killing by the complement machinery and presented a rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…This study showed that the mutants not only retained the deletion of one allele but also remained in the original locus. Thus, the mutation was stable, without demonstrable reversion to the wild-type genotype, even after longterm infection cycle in the mammalian host [145]. Similar results using this approach were obtained by Zago et al for lyt1 mutants [131] and by Basombrío et al [129] for a gp72 mutant.…”
Section: Genome Plasticity Stability and Safety Of The Engineered Locussupporting
confidence: 79%
See 2 more Smart Citations
“…This study showed that the mutants not only retained the deletion of one allele but also remained in the original locus. Thus, the mutation was stable, without demonstrable reversion to the wild-type genotype, even after longterm infection cycle in the mammalian host [145]. Similar results using this approach were obtained by Zago et al for lyt1 mutants [131] and by Basombrío et al [129] for a gp72 mutant.…”
Section: Genome Plasticity Stability and Safety Of The Engineered Locussupporting
confidence: 79%
“…Necropsies at day 60 post infection revealed that mice immunized with mutant parasites showed reduced inflammatory response in heart and muscle tissues, compared to controls. Also, the spleen index was significantly reduced in mutant and wild-type TCC immunized mice [145]. Taken together, these results showed that TcCRT+/À parasites were limited in two major properties conferred by TcCRT and indirectly by C1q: the capacity to evade the host immune response and their virulence status.…”
Section: Calreticulinmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, parasites carrying a monoallelic deletion of the TcCRT gene, are significantly susceptible to complement-mediated lysis. As expected, parasites overexpressing TcCRT are significantly more resistant to the complement-mediated lysis by CP and LP ( Sanchez-Valdez et al, 2013 , 2014 ).…”
Section: Trypanosoma Cruzi Calreticulin An Important Virulesupporting
confidence: 70%
“…In addition, TcCRT plays a central role during the host-parasite interplay by interacting with complement proteins such as complement factor ( C 1), mannose-binding lectin (MBL), and ficolins to inhibit activation of the complement system that leads to increased infectivity of the parasite (Lopez et al, 2010, Ramirez et al, 2011b, Sosoniuk et al, 2014). This indicates that TcCRT does not only act as a virulence factor (Sanchez-Valdez et al, 2014) to persist, sustain and promote infectivity but also inhibits growth and metastasis of tumors. A further study has demonstrated that some T. cruzi strains are able to respond to oxidative stress caused by DNA damaging agents (Campos et al, 2011, Grazielle-Silva et al, 2015).…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%